Portability of online reputation: Business and technical perspectives - Duan, Zhuosong (University of Ottawa (Canada), 2008)
Trust plays a crucial role in online commerce, collaboration and interactions in general. Reputation systems have emerged in recent years as a technology and tools for fostering trust in online interactions. These community tools help people make decisions on whom they can trust, encourage trustworthy behavior, and preclude dishonest and unskilled participants. Despite their successful use, today's reputation systems face many problems, one of which is the lack of portability. Since every existing reputation system is bound to a specific website, a user's reputation is locked in one community only, making the user unable to use that reputation outside the community. Portable reputation systems will solve this problem by making a user's reputation information accessible to any online entities s/he wishes to interact with. This thesis introduces the concepts of trust, online trust and reputation, introduces reputation systems, analyzes the importance of trust and reputation systems in online interactions, conducts a study on portability of online reputation, and proposes a model for reputation system which supports the feature of portability.
Keywords: Information Science.; Engineering, System Science.